ANALYSIS OF THE IMPLEMENTATION OF LEAN MANAGEMENT METHOD TO IMPROVE PATIENT SATISFACTION (CASE STUDY OF HEART AND BLOOD VESSEL OUTPATIENT PATIENTS PARTICIPANTS OF BPJS KESEHATAN AT SYARIFAH AMBAMI RATO EBU BANGKALAN REGIONAL HOSPITAL) - Muhammad Jauhari Wafi; Taufik Zulfikar; Rulia; Rukhiyat Syahidin; Vip Paramarta; Kosasih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Outpatient cardiovascular services are among the healthcare services with high patient volumes, which may lead to process inefficiencies and decreased patient satisfaction, particularly among BPJS Health Insurance participants. Lean Management is considered a strategic approach to improving service efficiency and patient satisfaction through Waste elimination and continuous improvement. This study aimed to analyze the implementation of Lean Management, identify types of Waste, examine its impact on patient satisfaction, and explore the role of strategic management in supporting the sustainability of Lean Management in the outpatient cardiovascular clinic of RSUD Syarifah Ambami Rato Ebu Bangkalan. This study employed a qualitative design with a case study approach. Informants were selected using purposive sampling and included hospital management, healthcare staff, and patients. Data were collected through in-depth interviews, observations, and document review, and analyzed using thematic analysis. The results showed that Lean Management had been implemented through the application of Just-In-Time principles, 5S culture, Kaizen, and service digitalization. The main types of Waste identified were waiting time, administrative duplication, and service flow Bottlenecks. The implementation of Lean Management had a positive impact on patient satisfaction, particularly in terms of service flow clarity, procedural simplicity, and staff attitudes. However, waiting time and physical facility comfort remained key challenges.